Prophylactic Mesh Application during Colostomy to Prevent Parastomal Hernia: A Meta-Analysis - JunJia Zhu; YuWei Pu; XiaoDong Yang; DeBao Zhang; Kui Zhao; Wei Peng; ChunGen Xing (Gastroenterology Research and Practice)
Background. Parastomal hernia is a common complication after stoma formation, especially in permanent colostomy. The present meta-analysis aimed to evaluate the effectiveness of prophylactic mesh application during permanent colostomy for preventing parastomal hernia. Methods. Randomized controlled trials comparing outcomes in patients who underwent colostomy with or without prophylactic mesh application were identified from PubMed, EMBASE, Science Citation Index, and the Cochrane Libraries. Results. This meta-analysis included 8 randomized controlled trials with 522 participants. Our pooled results showed that prophylactic mesh application (mesh group) reduced the incidence of clinically detected parastomal hernia (risk ratio [RR]: 0.22; 95% confidence interval [CI]: 0.13–0.38; P<0.00001), radiologically detected parastomal hernia (RR: 0.62; 95% CI: 0.47–0.82; P=0.0008), and surgical repair for herniation (RR: 0.34; 95% CI: 0.14–0.83; P=0.02) when compared with conventional permanent colostomy formation (control group). The incidence of complications, including wound infection, peristomal infection, mesh infection, stomal necrosis and stenosis, stoma site pain, and fistula, was not higher in the mesh group than in the control group. Conclusions. Our meta-analysis demonstrated that prophylactic mesh application at the time of primary colostomy formation is a promising method for the prevention of parastomal herniation.